Méthodes d'investigation de l'alimentation et des mangeurs - Lepiller, Olivier; Fournier, Tristan; Bricas, Nicolas; Figuié, Muriel (éditions Quae, 2021)
Researchers rarely reveal the details of the methodological choices that underpin their research. The theoretical and practical considerations that have guided them in these choices often remain implicit. In this book, the methods for studying food and 'eaters' are central. The use of the term 'eaters' aims to distinguish them from the figure of the consumer. It emphasises the multidimensionality of the act of eating, an act that engages the biological body as much as the sociality of individuals and inserts them into space and time as well as into economic exchanges. This book is the result of a collective effort involving some forty experienced researchers. With a view to pedagogy, it aims to critically present fifteen methods currently used in or at the crossroads of different disciplines: anthropology, economics, geography, nutrition and sociology. The book will be of interest to students, teachers, expert researchers and other professionals looking for methods to better understand or refine their own tools for studying food and eaters.